Design, construction, and preliminary results of a 250-kW organic Rankine cycle system. (5th April 2015) - Fu, Ben-Ran; Lee, Yuh-Ren; Hsieh, Jui-Ching
Abstract: This study involved designing and constructing a 250-kW organic Rankine cycle system, consisting of a pump, preheater, evaporator, turbine, generator, condenser, as well as hot and cooling water circulation systems. Refrigerant R245fa was used as a working fluid. The design operating pressure levels of the preheater/evaporator and condenser was 1.265 MPa and 0.242 MPa, respectively. Under design conditions, the net power output was 243 kW and the system thermal efficiency was 9.5%. The preliminary experimental results under off-design conditions showed that the average net power output was 219.5 kW with a fluctuation of ±5.5 kW during prolonged operation. The maximal net power output and system thermal efficiency were 225 kW and 7.94%, respectively. Under this condition, the isentropic efficiency of the turbine was 63.7% with a rotational speed of 12 386 rpm, and the back-work ratio was 6.7%. In addition, the results of the dynamic testing demonstrated that the present system responded very rapidly as the heat source temperature changed. The experimental results also demonstrated that the system thermal efficiency and net power output increased linearly with an increasing heat source temperature. However, the effect of the heat source temperature on the turbine efficiency was not obvious. Highlights: A 250-kW ORC system using turbine expander was studied for waste heat recovery. The experimentally maximal net power output was 219.5 ± 5.5 kW. The experimentally maximal system thermal efficiency was 7.94%. The turbine isentropic efficiency was 63.7% with a rotational speed of 12, 386 rpm. The system responded very rapidly as the heat source temperature changed.